The Body, Food and Eating - Wójtewicz, Anna; Maj, Agnieszka (The Body and Sociology – empirical research and theoretical concepts, 2026)
The aim of this chapter is to demonstrate selected links between socio-cultural construction of the body and the food understood as practice resulting from the biological need, and simultaneously, entangled in cultural terms. Consuming food and drinking are socially regulated. Society influences the form of food, its kind and amount as well as rituals related to food consumption. The regulations translate into such body qualities as body size, desired body shape, or weight. The related social expectations change depending on the epoch and culture.This chapter describes classic works of authors exploring food and eating as a cultural activity. Some of them may be considered an achievement of both cultural anthropology and sociology.The text offers an explanation as to why the issues relating to the body and food were absent for so long in sociology. New directions in the reflection on these areas are also indicated, necessarily focusing solely on selected issues. The discussion includes such subject areas as, inter alia, the body, food and eating, and social inequalities (including gender-based), referring to the works of such authors as Norbert Elias, Pierre Bourdieu or Chris Shilling. Moreover, the contents of this chapter refer the reader to the descriptions and analyses of issues that frequently affect in a direct manner people living in contemporary society. In particular, we would like to indicate the issue of dietary regimens and the necessity to function in the so-called diet culture, in which how we look, what we eat and what exercises we perform are treated as a display of moral virtues. At the end of the chapter, areas of research related to the body and food in contemporary sociology are indicated and the most important concepts are listed that may be helpful in further study of the body and food.